ANALISIS TINGKAT LITERASI KEUANGAN SISWA SMA KRISTEN SATYA WACANA - Destri Sambara Sitorus (ECOBISMA (JURNAL EKONOMI, BISNIS DAN MANAJEMEN), 2021)
Good financial literacy is very important for everyone to have because it will help manage finances and create prosperity. This study aims to determine the level of financial literacy of Satya Wacana Christian High School students. The aspect of financial literacy studied is knowledge of personal finances, savings and savings, and investment. This research is a descriptive study and data were collected using a questionnaire. The population in this study were all Satya Wacana Christian High School students. The research sample of 90 students was carried out by using random sampling technique. The results showed that the level of financial literacy of Satya Wacana Christian Senior High School students was 54.29% in the low category.Â Keywords: Financial literacy, student.